2016
DOI: 10.3892/mco.2016.892
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a trastuzumab-containing treatment regimen for patients with unresectable advanced or recurrent gastric cancer

Abstract: Abstract. The present study aimed to evaluate the efficacy and safety of trastuzumab plus chemotherapy for patients with unresectable advanced or recurrent gastric cancer. A retrospective analysis of 213 patients with unresectable advanced or recurrent gastric cancer who received systemic chemotherapy, including 15 patients who were also administered trastuzumab, at Kochi Medical School between 2007 and 2013 was performed. The overall survival was compared between patients who received trastuzumab plus chemoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
2
10
0
1
Order By: Relevance
“…Interestingly, HER2 overexpression levels were similar in patients from Europe and Asia, whereas they were lower in patients from Central/South America. Overexpression or amplification of HER2 was more common in intestinal GCs than diffuse or mixed types of GC, which was in concordance with other studies [45,46]. In addition, GEJ tumors showed higher rate of HER2 overexpression or amplification than stomach tumors, indicating that GEJ adenocarcinoma differs in etiology and pathogenesis from distal stomach tumors.…”
Section: Monoclonal Antibodiessupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, HER2 overexpression levels were similar in patients from Europe and Asia, whereas they were lower in patients from Central/South America. Overexpression or amplification of HER2 was more common in intestinal GCs than diffuse or mixed types of GC, which was in concordance with other studies [45,46]. In addition, GEJ tumors showed higher rate of HER2 overexpression or amplification than stomach tumors, indicating that GEJ adenocarcinoma differs in etiology and pathogenesis from distal stomach tumors.…”
Section: Monoclonal Antibodiessupporting
confidence: 91%
“…These findings pointed out clinically important aspect, which could underlie the discrepancy between studies and clinical trials, evaluating the benefit of anti-HER2 targeted chemotherapies. First, HER2 expression patterns differ between GC and breast cancer and furthermore, in GC the expression patterns are frequently heterogeneous [44,46,86,88]. The optimal cutoff for selecting patients with GC who would benefit from addition of lapatinib to chemotherapy should be evaluated in further studies; however, at present, the results indicated that the cutoff value, based on FISH assays, could be the ratios 5.01-10.0 and >10.0 [86].…”
Section: Small-molecule Compoundsmentioning
confidence: 90%
“…Trastuzumab, a monoclonal antibody that targets HER2, is one of a mere few targeted therapies that have been used in human gastric cancer [17, 18]. Trastuzumab could partly prolong survival and improve the quality of life of gastric cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Zračenje takođe ima ograničeni učinak. Biološka terapija se testira u lečenju karcinoma želuca, cetuksimab, ramucirumab, trastuzumab i fosfolipaza D1 antitela obećavaju u rezultatima lečenja HER2 pozitivnih pacijenata sa karcinomom želuca [18,19,20].…”
Section: Discussionunclassified